Nonprofit Wages: Theory and Evidence - Barry Hirsch; David A. Macpherson; Anne E. Preston (Institute of Labor Economics (IZA), 2017)
The nonprofit sector's share of wage and salary employment in the U.S. has increased over time, from about 5 percent in the mid-1990s to 7 percent in 2015. This paper surveys the literature and presents new evidence on the employment and earnings of workers in the nonprofit sector since 1994. As compared to the private for-profit sector, nonprofits have a more educated and older workforce, with employment concentrated in health, education, and service occupations and industries. Standard wage level analysis indicates lower wages for men employed in nonprofits compared to male for-profit workers with similar measured attributes. No such penalty is found for women. Based on panel estimates of wage changes, we find no substantive wage penalties for either women or men moving between jobs in and outside the nonprofit sector. We conclude that wages in the nonprofit and for-profit sectors, on average, differ little for similar workers and jobs.
Keywords: J21; J31; L33; 330; nonprofit wage differentials; nonprofit employment; Current Population Survey (CPS)